Komunikasi Interpesonal Guru Dalam Pembentukan Karakter Siswa - Adli Adli; Tami Septiani; Agus Srimudin (UNIVERSITAS PAKUAN, 2024)
Interpersonal communication is an interaction activity that we often encounter in everyday life, one of which is interaction between teachers and students. Interpersonal communication can influence human behavior such as personal character. The Special High School for the Mentally Disabled by Karya Ibu Palembang is an educational forum for mentally disabled students who have limited IQ and whose task is to build the students' character. This research aims to analyze teacher interpersonal communication in the formation of students' character and obstacles. The method used in this research is a descriptive qualitative method, which tries to describe the object being studied based on facts in the field. The results of this research show that interpersonal communication between teachers and students in the formation of personal character can be obtained through openness, empathy, supportive attitudes, and positive attitudes, while equality in teacher and student interactions cannot influence self-character. In the interpersonal communication process, there are also barriers to interpersonal communication between teachers and students such as process, physical, psychological, and technical barriers.